Adaptation Strategies of Traditional Handline Fishermen to Coastal Reclamation in Sario District - Makaluas, Marselino M.; Manoppo, Victoria; Mamangkey, Noldy G. F.; Luasunaung, Alfret; Mandagi, Ixchel F.; Malalantang, Sjenny S.; Sumilat, Deiske A. (Sam Ratulangi University, 2025)
Coastal reclamation in Sario District since 1995 has affected the socioeconomic conditions of coastal communities, particularly handline fishermen. This study aims to identify the socioeconomic conditions of fishermen, analyze internal and external factors using PESTEL and SWOT analyses, and determine appropriate adaptation strategies. The research was conducted from August to November 2025 in three villages within Sario District using a descriptive qualitative and quantitative approach. Results show that fishermen are mostly of productive age with low education levels. Declining income due to distant fishing grounds has driven diversification into side jobs. The PESTEL analysis revealed impacts of reclamation, rising costs, and weak marketing, while SWOT placed fishermen in an aggressive strategy position with strong internal capacity but serious external threats. Adaptive strategies involve pursuing side jobs while preserving traditional fishing livelihoods. Keywords: adaptation strategy; traditional fishermen; coastal reclamation; handline fishing; PESTEL analysis; SWOT analysis Abstrak Reklamasi pantai di Kecamatan Sario sejak 1995 berdampak pada kondisi sosial ekonomi masyarakat pesisir, terutama nelayan pancing ulur. Penelitian ini bertujuan mengidentifikasi kondisi sosial ekonomi nelayan, menganalisis faktor internal dan eksternal menggunakan PESTEL dan SWOT, serta menentukan strategi adaptasi yang tepat. Penelitian dilakukan selama Agustus–November 2025 di tiga kelurahan di Kecamatan Sario dengan pendekatan deskriptif kualitatif dan kuantitatif. Hasil menunjukkan nelayan didominasi usia produktif dan berpendidikan rendah. Penurunan pendapatan akibat jauhnya area tangkap mendorong diversifikasi pekerjaan. Analisis PESTEL mengungkap dampak reklamasi, biaya tinggi, dan lemahnya pemasaran, sementara SWOT menempatkan nelayan pada strategi agresif dengan kekuatan internal baik namun menghadapi ancaman eksternal. Strategi adaptasi dilakukan melalui pekerjaan sampingan tanpa meninggalkan profesi tradisional. Kata kunci: strategi adaptasi; nelayan tradisional; reklamasi pantai; pancing ulur; analisis PESTEL; analisis SWOT